Injuries in professional motor car racing drivers at a racing circuit between 1996 and 2000. Issue 5 (23rd September 2004) - Minoyama, O; Tsuchida, H
Abstract : Background: Research on injuries in racing drivers is limited. Objective: To gain more information about such injuries. Methods: Injuries recorded during and after races between 1996 and 2000 were investigated using the medical charts from the circuit medical centre at Fuji Speedway, which is one of the biggest circuits in Japan. Races were in either single seat/formula cars or saloon cars. Results: Data were obtained from 39 races in single seat cars (1030 participating cars) and 42 races in saloon cars (1577 cars). Fifty injuries were recorded during the single seat car races, and 62 during the saloon car races (injury rate 1.2 per 1000 competitors per race and 0.9 per 1000 competitors per race respectively). Thirteen injuries were recorded after the race, 12 of them in saloon car racing. Bruises were the major injury in single seat car racing (58%). Lower limb bruising was more common than upper limb bruising. Most of the injuries in saloon car racing (53.2%) were neck sprains. The incidence of concussion was high in both groups compared with other high risk sports. Conclusions: There were some differences in injuries between the two types of car. No serious injuries occurred except for one death. However, the driver's body is subjected to large forces in a crash, hence the high incidence of concussion. The injuries recorded after the race emphasise that motor racing is a demanding sport.